evidence-based consensus for the classification of arbuscular mycorrhizal fungi (Glomeromycota) - Redecker, Dirk; Schüßler, Arthur; Stockinger, Herbert; Stürmer, Sidney L; Morton, Joseph B; Walker, Christopher (Mycorrhiza, 2013)
The publication of a large number of taxon names at all levels within the arbuscular mycorrhizal fungi (Glomeromycota) has resulted in conflicting systematic schemes and generated considerable confusion among biologists working with these important plant symbionts. A group of biologists with more than a century of collective experience in the systematics of Glomeromycota examined all available molecular–phylogenetic evidence within the framework of phylogenetic hypotheses, incorporating morphological characters when they were congruent. This study is the outcome, wherein the classification of Glomeromycota is revised by rejecting some new names on the grounds that they are founded in error and by synonymizing others that, while validly published, are not evidence-based. The proposed “consensus” will provide a framework for additional original research aimed at clarifying the evolutionary history of this important group of symbiotic fungi.